Does 'flight shame' affect social norms? Changing perspectives on the desirability of air travel in Germany. (1st September 2020) - Gössling, Stefan; Humpe, Andreas; Bausch, Thomas
Abstract: 'Flight shame' describes an unease about the climate implications of air travel, and bears evidence of a change in social norms that have so far associated flying with social status. This paper discusses whether Fridays for Future demonstrations and ensuing flight shame have influenced social norms regarding the desirability of air travel, and whether this is measurable in a decline in air travel, or policy support for measures curbing emissions from aviation. These aspects are discussed on the basis of German flight statistics and an online panel survey (n = 1002) conducted in August 2019 in Germany. Results show that, against a background of falling domestic air transport demand, respondents do not report a significant change in travel behaviour. However, a two-third majority of respondents indicate support for market-based measures increasing the cost of flying, as well as policies forcing airlines to reduce emissions and legislation abolishing subsidies. These findings point at an ongoing change in social norms, which could be reinforced if policymakers took advantage of public support for ambitious climate policies. Highlights: Investigates flight shame debates' influence on social norms and policy support. Finds strong evidence of a heightened awareness of air travel implications. Suggests that social practice change is already visible in declining passenger numbers. Affirms support for far-reaching climate policies to curb emissions from aviation.